Graduate database system - Gaddam, Srikanth (Kansas State University, 2011)
Education plays a very important role in molding a person into a good individual by imparting knowledge in all aspects. Globalization has helped the students to go to different countries, attain knowledge and exposure on the culture of that country. Universities receive several hundreds of applications from all over the world to get admission for higher studies. By following the conventional method the faculty of the university and also the applicant will face lot of difficulties in communicating. In conventional method the acceptance or rejection would be generally intimated through post. The applicant will be in complete ignorance during the processing of application. They will be several scenarios where interaction between them is necessary to further process the application. This project is intended to overcome such problems and make the interaction between the staff and applicant smoother. The main objective of the project is to develop a website for Computing and Information Sciences department which manages the data regarding the prospective students as well as students currently enrolled. It can be accessed by prospective students (who wish to join the university), faculty and administrators. Applicant will be notified constantly through email and they can always check their application status online. The role of the administrators is to accept applications sent by prospective students and upload their details such as their GRE, TOEFL scores and their academic records into the database. Once these details are stored in the database, the students will be able to access their application status. Students are also given information about missing documents in the database. There will be a committee to decide the application status whether it will be rejected or accepted. Once the applicant is accepted, the applicant would be added to the current students list. All this process is made easy through this website.
Keywords: Graduate; Database; Computer Science (0984)